Effect of Orthographic Processes on Letter Identity and Letter-Position Encoding in Dyslexic Children - Reilhac, Caroline; Jucla, Mélanie; Iannuzzi, Stéphanie; Valdois, Sylviane; Démonet, Jean-François (Frontiers in Psychology, 2012)
The ability to identify letters and encode their position is a crucial step of the word recognition process. However and despite their word identification problem, the ability of dyslexic children to encode letter-identity and letter-position within strings was not systematically investigated. This study aimed at filling this gap and further explored how letter identity and letter position encoding is modulated by letter context in developmental dyslexia. For this purpose, a letter-string comparison task was administered to French dyslexic children and two chronological-age (CA) and reading-age (RA)-matched control groups. Children had to judge whether two successively and briefly presented 4-letter-strings were identical or different. Letter-position and letter-identity were manipulated through the transposition (e.g., RTGM vs. RMGT) or substitution of two letters (e.g., TSHF vs. TGHD). Non-words, pseudo-words and words were used as stimuli to investigate sub-lexical and lexical effects on letter encoding. Dyslexic children showed both substitution and transposition detection problems relative to CA controls. A substitution advantage over transpositions was only found for words in dyslexic children whereas it extended to pseudo-words in RA controls and to all type of items in CA controls. Letters were better identified in the dyslexic group when belonging to orthographically familiar strings. Letter position encoding was very impaired in dyslexic children who did not show any word context effect in contrast to CA controls. Overall, the current findings point to a strong letter identity and letter position encoding disorder in developmental dyslexia.